The Adult Hip - Master Case Series and Techniques (Springer International Publishing, 2018)
This book is intended to offer a "virtual fellowship" in hip surgery that will give readers the opportunity to join distinguished hip surgeons in the operating room, learning key points and solutions to technical difficulties from the beginning to the end of 100 surgical cases. All of these cases have been carefully selected by renowned orthopaedists who work at the world's top centers and perform surgery based on evidence. To facilitate quick learning, the cases are presented using a uniform template, guiding the reader from clinical evaluation and preoperative planning, through the decision-making process, to the surgical procedure and the final outcome. At the end of each case, the editor invites the surgeon to answer specific questions in order to further elucidate crucial issues with reference to current evidence. The book is divided into four sections: conservative hip surgery, primary hip arthroplasty, complex hip arthroplasty, and revision arthroplasty. It will be of value across the world to specialist hip surgeons and surgeons in training who are interested in hip surgery.